2001
DOI: 10.1002/mrd.1002
|View full text |Cite
|
Sign up to set email alerts
|

Involving AP‐2 transcription factor in connexin 26 up‐regulation during pregnancy and lactation

Abstract: Gap junction connexin 26 (Cx26) is up-regulated in mammary epithelial cells during pregnancy and lactation. To understand the transcriptional regulation of Cx26, we identified a protected DNase I footprint region (-140 to -113) in the rat Cx26 promoter. This rCx26 Promoter Footprinting Region, or CPFR, contains an Sp binding site (CCGCCC) overlapping with an AP-2 binding site (GCCCGCGGC), and is evolutionarily conserved. Nuclear extracts from rat mammary glands and human MCF-10 mammary epithelial cells formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Furthermore, connexin-26 expression is confined to the alveolar epithelium, specifically localized to where adjacent alveolar cells are in contact (Locke et al, 2000). A functional binding site for the AP-2 transcription factors has been identified in the connexin-26 promoter (Tu et al, 2001), indicating that our transcript-profiling experiment may have found at least one transcription factor cascade following PRL binding to its receptor on mammary epithelial cells.…”
Section: Mammary Transcriptional Response To Prlmentioning
confidence: 79%
“…Furthermore, connexin-26 expression is confined to the alveolar epithelium, specifically localized to where adjacent alveolar cells are in contact (Locke et al, 2000). A functional binding site for the AP-2 transcription factors has been identified in the connexin-26 promoter (Tu et al, 2001), indicating that our transcript-profiling experiment may have found at least one transcription factor cascade following PRL binding to its receptor on mammary epithelial cells.…”
Section: Mammary Transcriptional Response To Prlmentioning
confidence: 79%
“…Overexpression of Nkx2.5, a member of the NK2 homeodomain proteins was associated with a decrease in Cx43 expression, suggesting that Nkx2.5 may function as a transcriptional repressor (52). SP1 has also been found involved in the transcriptional regulation of Cx26, in rat mammary gland and uterus, as well as in the activation of Cx40 and Cx32 proximal promoter (53)(54)(55). Moreover, it has been demonstrate that Sox10, a transcription modulator, activates Cx32 expression (56).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the human sequence contains a YY1-like binding site and a consensus mammary gland factor binding site (276). The region Ϫ140 to Ϫ113 of the Cx26 promoter includes an Sp binding site overlapping with an AP-2 binding site which are responsible for the upregulation of Cx26 in the myometrium during pregnancy and in the mammary gland during lactation (590).…”
Section: Transcriptional Regulation and Gene Promotersmentioning
confidence: 99%